2014
DOI: 10.3126/njog.v3i2.10832
|View full text |Cite
|
Sign up to set email alerts
|

Age as risk factors associated in the genesis of uterovaginal prolapse (UVP)

Abstract: Aim: To find out the relationship between utero-vaginal prolapse (UVP) and first vaginal birth at younger age <22 years and to identify single most frequently occurred risk factor in study group. Method: A hospital based descriptive comparative study was carried out in 200 women of age 40- 60 years in two hospitals. One hundred women with UVP were enrolled as case (Group I) and 100 women with similar parity and age group but admitted for other reasons than prolapse were enrolled as comparative group (Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…14 Pandit et al reported that though cases were more likely than controls to have a low BMI<18kg/m 2 , it was not statistically signifi cant. 7 Studies from the West show increased risk of prolapse with increasing BMI but studies in our part of the world including the present study show that being underweight is a signifi cant risk factor for prolapse. This difference is probably a refl ection of the difference in nutritional status of the women, obesity becoming an epidemic in the West while our women are still malnourished.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…14 Pandit et al reported that though cases were more likely than controls to have a low BMI<18kg/m 2 , it was not statistically signifi cant. 7 Studies from the West show increased risk of prolapse with increasing BMI but studies in our part of the world including the present study show that being underweight is a signifi cant risk factor for prolapse. This difference is probably a refl ection of the difference in nutritional status of the women, obesity becoming an epidemic in the West while our women are still malnourished.…”
Section: Discussioncontrasting
confidence: 52%
“…4 Vaginal childbirth, young age at fi rst childbirth, frequent childbirths, advancing age, and increasing body-mass index are the most consistent risk factors associated with prolapse. [5][6][7][8][9][10] While the reproductive risk factors are mostly blamed, other non-reproductive factors like family history, obesity, smoking, medical disorders like chronic cough/ chronic obstructive pulmonary disease (COPD), constipation are also emerging as important risk factors in the West where reproductive factors are on a decline. 11,12 This study was done to see whether the non-reproductive factors play a role in causation of prolapse in our women.…”
Section: Introductionmentioning
confidence: 99%
“…The most important once are factors that increase intra-abdominal pressure, di cult labor and delivery, malnutrition, old age, connective tissue disorders, heavy exercise, and pelvic trauma are associated with UVP (7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature around the world revealed different factors for the development of uterovaginal prolapse. The most important once are factors that increase intra-abdominal pressure, di cult labor and delivery, malnutrition, old age, connective tissue disorders, heavy exercise, and pelvic trauma [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%